Preparation of film material based on covalent organic frameworks (COFs) and application of film material in water-based zinc ion battery negative electrode protection
The COFS film material is legally prepared through the liquid-liquid interface, and it is applied to the negative electrode of the zinc ion battery of the water system, solving the problem of zinc branch crystals and zinc corrosion, and realized the efficient battery cycle stability and electrochemical energy storage performance.
Patent Information
- Application Number
- CN202411664446.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
During the circulation process, the negative electrode of the aqueous zinc ion battery is prone to zinc dendrites and zinc corrosion, which limits the application of materials in the negative electrode protection of the battery.
Prepare the COFS film material based on the covalent-based organic framework of covalent-based organic framework through the liquid-liquid interface aggregation method, and use the alda-based phenyl-based compounds as the structural unit to regulate the monomer Murbi and the response conditions to prepare a COFS thin film material with a thickness of one thickness. And the acetone solvent pulls it to the zinc foil as a protective layer.
The application of COFS thin film materials in the protection of the negative protection of the zinc ion battery of water system, effectively suppress zinc branches and zinc corrosion, improves the cycle stability of the battery, and improves the electrochemical energy storage performance by regulating the crystal surface and the size of the tunnel. Essence
Smart Images

Figure CN119371617A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional polymer materials, and in particular relates to the preparation of a covalent organic framework (COF) thin film material and its application in the protection of negative electrodes of aqueous zinc ion batteries. Background Art
[0002] With the continuous growth of global energy demand and the gradual depletion of traditional fossil fuel resources, the development of renewable energy has become an important issue worldwide. Renewable energy is environmentally friendly, sustainable, and cheap. It can effectively reduce greenhouse gas emissions, solve energy security problems, and promote sustainable economic development. In order to achieve large-scale storage and stable output of renewable energy, it is essential to develop high-performance energy storage equipment that matches it. However, with the continuous development of the new energy field, electrochemical energy storage, which mainly features excellent cycle stability, good charge and discharge efficiency, environmentally friendly, and low material cost, has gradually become the focus of the future energy storage field.
[0003] COFs are a class of high-surface-area crystalline organic porous polymer materials formed by light elements connected by reversible covalent bonds. Compared with other disordered porous organic polymers (such as conjugated microporous polymers (CMP), hypercrosslinked polymers and porous aromatic framework compounds), they present a more regular one-dimensional pore structure and a highly ordered skeleton structure, which not only has the potential to fully utilize their high specific surface area in the energy storage process, but also lays a solid structural foundation for the precise functionalization of the microstructure of this type of material. Due to the intrinsic properties of COFs materials, the solvothermal method is currently the main method for synthesizing COFs materials, but the solvothermal method can only prepare powdered materials, which limits its application in the negative electrode protection of aqueous zinc-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to prepare a covalent organic framework (COFs) thin film material for protecting the negative electrode of an aqueous zinc ion battery and solving problems such as zinc dendrites and zinc corrosion that occur at the negative electrode during battery cycling.
[0005] 1. A structure of a covalent organic framework COFs thin film material is:
[0006]
[0007] 2. Controllable preparation method based on covalent organic framework thin film materials
[0008] COFs thin film materials include covalent organic crystal thin film materials TpPa-COFs or thickness-controllable yellow covalent organic crystal thin film materials FCOFs, which are prepared by using compounds containing aldehyde groups and amino groups as monomers, utilizing Schiff base reaction, and a liquid-liquid interfacial polymerization method, wherein the mass ratio of the two reaction monomers is 3.75-15.7:4.4-20.8 (mg); the reaction temperature is 25-30°C, and the reaction time is 48-72h; wherein, by regulating the molar ratio of the two reaction monomers, thin film materials of different thicknesses can be obtained; by controlling the reaction time, reaction temperature and the type of catalyst, the reaction rate is controlled to prepare a thin film material with uniform thickness, which is then transferred to any substrate by an acetone solvent drawing method.
[0009] In the phenyl compounds containing aldehyde functional groups, heteroatoms F atoms, N atoms, or Cl atoms are introduced to regulate the charge distribution of the entire monomer molecule, so as to protect the zinc negative electrode while regulating the zinc foil crystal surface, making it more conducive to Zn 2+ The horizontally deposited crystal faces are exposed.
[0010] There are 6 kinds of phenyl compounds containing amino functional groups, which react with 6 kinds of monomers containing aldehyde groups respectively. By controlling their molar amounts, they react fully with the aldehyde monomers to prepare a film with uniform thickness; wherein the aldehyde monomers are:
[0011]
[0012] The amine monomers are:
[0013]
[0014] X is C or N.
[0015] 1. A method for preparing a covalent organic crystal thin film material TpPa-COFs, comprising the following steps:
[0016] Step (1) uses trihydroxybenzene trimaldehyde (Tp) and p-phenylenediamine (Pa) as raw materials, and forms nanoparticles at the interface between the two phases through liquid-liquid interfacial polymerization and adjustment of the polarity of the reaction solvent;
[0017] In step (2), under the reaction conditions of 25-30° C., the oligomer nanoparticles undergo a reversible Schiff base reaction, and under the action of a catalyst, a covalent organic crystal thin film material TpPa-COFs is formed at the interface over time.
[0018] Wherein, in step (1), the mass ratio of trihydroxybenzene trimeraldehyde to p-phenylenediamine molecular monomers is 3.75-15.7:4.4-20.8 (mg), and at the initial stage of the reaction, acetonitrile solvent (8 ml) is added to the aqueous phase.
[0019] In step (2), the trihydroxybenzene trimethylene oxide in step (1) is dissolved in 25-50 ml of dichloromethane to form an organic phase, and p-phenylenediamine is dissolved in 25-42 ml of deionized water to form an aqueous phase; the aqueous phase is slowly added dropwise to the organic phase, and 2.5-4.5 ml of 2M p-toluenesulfonic acid is added as a catalyst, and the mixture is allowed to stand for 48-72 hours at 25-30° C.; the prepared film is washed and dried with acetone, anhydrous ethanol and deionized water, respectively, to finally obtain the above-mentioned covalent organic crystal film material TpPa-COFs.
[0020] The liquid-liquid interfacial polymerization method is used to control the reaction rates of the two monomers. In the initial stage of the reaction, the growth mode of the oligomers is changed with the inductive effect of the reaction solvent, thereby forming nanoparticles at the interface. As time goes by, under the action of the catalyst, a covalent organic crystal thin film material TpPa-COFs is gradually formed at the interface of the two phases. This not only effectively controls the monomer reaction rate, but also effectively solves the problem that only powdered COFs materials can be prepared due to the limitations of the intrinsic properties of the material, thus realizing the application of COFs thin film materials in the negative electrode protection of aqueous zinc-ion batteries.
[0021] 2. A method for preparing a thickness-controllable yellow covalent organic crystal thin film material FCOFs, specifically:
[0022] 10.5-25 mg 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 8.5-23 mg 2,3,5,6-tetrafluoroterephthalaldehyde (TFTA) are used as raw materials, directly dissolved in a mixed solvent of 1,4-dioxane and mesitylene (4:1-3:2, V:V, 50 ml), and ultrasonically treated at room temperature until the monomers are completely dissolved to form an organic phase; at the same time, 3-5 ml of 0.05 M scandium trifluoromethanesulfonate is added to 50 ml of deionized water as a catalyst, and this is used as the aqueous phase; the organic phase is slowly added dropwise into the aqueous phase, and the thin film formed at the interface is washed with acetone, anhydrous ethanol and deionized water by liquid-liquid interfacial polymerization, and then dried, and finally a yellow covalent organic crystal thin film material FCOFs with controllable thickness is obtained.
[0023] 3. Application of covalent organic frameworks (COFs) thin film materials in protecting the negative electrode of aqueous zinc ion batteries
[0024] The application method of the two prepared TpPaCOFs and FCOFs thin film materials as protective materials in the negative electrode of aqueous zinc ion batteries:
[0025] The prepared thin film material was transferred to zinc foil as a protective layer by acetone solvent drawing method, left to stand at room temperature to allow the acetone to fully evaporate, then thoroughly washed with deionized water, and after vacuum drying, assembled into paired cells, half cells, and full cells to measure their electrochemical energy storage performance.
[0026] The size of the film can be cut and matched according to the size of the zinc foil. The film can be transferred not only to the zinc foil, but also to the stainless steel foil, copper foil or titanium foil.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The COF thin film material of the present invention uses phenyl compounds containing aldehyde groups and amino groups as structural units, and is prepared by Schiff base reaction and liquid-liquid interface polymerization to obtain COFs thin film material. The conjugated structure and rich redox active groups of the material are conducive to rapid electron transfer. In addition, as a negative electrode protective material for aqueous zinc ion batteries, it has a good inhibitory effect on the side reactions (zinc dendrites, zinc corrosion, hydrogen evolution reaction) occurring at the negative electrode; at the same time, by screening monomers and introducing heteroatoms (such as F atoms), the crystal surface can be precisely regulated and the pore size can be controlled, thereby being selective for ions, and inducing Zn in the process of electroplating / stripping. 2+ Horizontal deposition is performed to improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 .Infrared spectra of hydroxybenzene trimeraldehyde (Tp), p-phenylenediamine (Pa), and TpPaCOFs;
[0030] Figure 2 .Infrared spectra of 1,3,5-tri(4-aminophenyl)benzene (TAPB), 2,3,5,6-tetrafluoroterephthalaldehyde (TFTA), and FCOFs;
[0031] Figure 3 .SEM images of pure zinc foil before and after cycling at 10,000x magnification;
[0032] Figure 4 .SEM images of zinc foil with protective film before and after cycling at 10,000x magnification;
[0033] Figure 5 .Nitrogen adsorption and desorption curves of TpPaCOFs;
[0034] Figure 6 .X-ray diffraction analysis of TpPaCOFs;
[0035] Figure 7 .Tafel diagram of half-cell composed of pure zinc foil and zinc foil with protective film;
[0036] Figure 8 .LSV diagram of half-cell composed of pure zinc foil and zinc foil with protective film;
[0037] Fig. 9 .Long cycle diagram of symmetrical battery composed of pure zinc foil and zinc foil with protective film;
[0038] Fig.10 .Cyclic voltammetry curves of full cells composed of pure zinc foil and zinc foil with protective film;
[0039] Fig.11 .Rate performance diagram of full battery composed of pure zinc foil and zinc foil with protective film;
[0040] Fig.12 .Long cycle stability diagram of full battery composed of pure zinc foil and zinc foil with protective film;
[0041] Fig.13 .X-ray diffraction analysis of FCOFs;
[0042] Fig.14 .Tafel diagram of half-cell composed of pure zinc foil and zinc foil with fluorine-based COF protective film;
[0043] Fig.15 .LSV diagram of half-cell composed of pure zinc foil and zinc foil with fluorine-based COF protective film;
[0044] Fig.16 .Long cycle diagram of symmetrical battery composed of pure zinc foil and zinc foil with fluorine-based COF protective film;
[0045] Fig.17 .Cyclic voltammetry curves of full cells composed of pure zinc foil and zinc foil with fluorine-based COF protective film;
[0046] Fig.18 : Rate performance diagram of a full battery composed of pure zinc foil and zinc foil with fluorine-based COF protective film. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with embodiments;
[0048] Example 1
[0049] A controllable preparation method based on a covalent organic framework thin film material, 8 mg of trihydroxybenzene trimethylene aldehyde is dissolved in 50 ml of dichloromethane as an organic phase, ultrasonically dissolved to make it completely dissolved as the bottom layer of the reaction solution, and 20 ml of deionized water is added to the upper layer as a spacer layer; at the same time, in another beaker, 10 mg of p-phenylenediamine is dissolved in a mixed solvent of deionized water and acetonitrile as an aqueous phase, ultrasonically dissolved to make it completely dissolved, and the solution is slowly dripped into the organic phase as the top layer of the reaction solution, and finally 3 ml of 2M p-toluenesulfonic acid is added to the aqueous phase as a catalyst, and it is sealed and left to stand at 25°C for 72 hours to ensure that there is no interference. The obtained product is repeatedly washed with acetone and deionized water, and the film is transferred to a zinc foil by an acetone solvent drawing method, and placed in a vacuum oven at 85°C for 12 hours to obtain the desired electrode material.
[0050] The synthesis of TpPaCOFs thin film material is as shown in the following route (1):
[0051]
[0052] The product obtained in Example 1 was tested and characterized for performance:
[0053] 1. Infrared spectrum of TpPaCOFs electrode material
[0054] from Figure 1 It can be seen that the infrared spectrum of COF film is at 1580cm -1 (C=C) and 1262cm -1 (CN) shows a stretching band at ∼3400 cm -1 The broad peak at 2892 cm is the OH stretching band of water molecules in the TpPa film, while the CH=O (2892 cm -1 ), C=O(1642cm -1 ) and NH(3198,3302,3373cm -1 ) stretching bands did not appear in the film, indicating the successful formation of the β-ketoenamine backbone structure, further demonstrating the formation of TpPaCOFs.
[0055] 2. Scanning electron microscope images of pure zinc foil before and after cycling
[0056] Figure 3 This is a scanning electron microscope image of pure zinc foil before and after cycling. As can be seen from the figure, after 50 cycles, the bare zinc electrode has undergone significant morphological changes, and the corrosion surface is full of vertically arranged zinc dendrites.
[0057] 3. Scanning electron microscope images of zinc foil with COFs protective film before and after cycling
[0058] Figure 4It is a scanning electron microscope image of pure zinc foil before and after cycling. As can be seen from the figure, after 50 cycles, for the COF@Zn electrode, after peeling off the COF protective layer, a denser morphology consisting of horizontally oriented Zn sheets was observed, indicating that the COF protective layer can indeed regulate the Zn 2+ deposition behavior and effectively inhibit the formation of Zn dendrites.
[0059] 4. Nitrogen adsorption and desorption curves of TpPaCOFs
[0060] like Figure 5 As shown in the figure, the TpPaCOFs were characterized by nitrogen adsorption-desorption isotherms at 77 K. As can be seen from the figure, the prepared material presents a type IV isotherm, revealing the characteristics of microporous materials. At the same time, the specific surface area and average pore size of the COFs material are 486 m 2 g -1 and 1.3nm.
[0061] 5. X-ray diffraction analysis of TpPaCOFs
[0062] like Figure 6 As shown in the figure, a main strong peak is observed at 2θ = 4.8° for TpPaCOFs, and its peak position corresponds to the (100) crystal plane. Two weak peaks at 2θ = 8.3° and 26.8° match the peak positions of the (110) and (001) crystal planes, respectively, and the higher PXRD peak intensity between the (100) and (001) crystal planes indicates that the π-π stacking of the material is more regular, which promotes the growth of microcrystals along the Z direction.
[0063] 6. Tafel curve of half-cell composed of pure zinc foil and zinc foil with protective film
[0064] Generally speaking, higher corrosion potential and lower corrosion current can reduce the corrosion rate of the electrode. Figure 7 It can be seen that the corrosion potential of the COF@Zn electrode is 1.01 V, while the corrosion potential of the bare zinc electrode is 0.998 V, indicating that the introduction of the COF protective layer can effectively alleviate the corrosion of the metal zinc anode.
[0065] 7. Linear polarization curve (LSV) of half-cell composed of pure zinc foil and zinc foil with protective film
[0066] Figure 8 Linear polarization is used to study the electrochemical hydrogen evolution corrosion of the electrode. As can be seen from the figure, the COF@Zn electrode shows a higher hydrogen evolution starting potential than the bare Zn electrode, indicating that the electrochemical hydrogen evolution corrosion of the electrode with the COF protective layer is inhibited.
[0067] 8. Long cycle diagram of symmetrical battery composed of pure zinc foil and zinc foil with protective film
[0068] like Fig. 9 As shown, at 0.5 mA cm -2 At a current density of 1.3 Å, the COF@Zn electrode exhibited a low voltage hysteresis of 17.8 mV and excellent stability over 200 h, while the bare Zn electrode had a short life of only 50 h. This demonstrates that good plating / stripping processes and Zn 2+ The rapid migration of the artificial protective layer also shows that the artificial protective layer has good durability and prolongs the cycle life of the battery.
[0069] 9. Cyclic voltammetry (CV) curves of full batteries composed of pure zinc foil and zinc foil with protective film
[0070] like Fig.10 , at 0.1mV s -1 At a scan rate of , COF@Zn||δ-MnO 2 and bare Zn||δ-MnO 2 The CV spectra of the COF@Zn electrode overlap well. At the same time, the battery with the COF@Zn electrode has a higher peak current than the battery with the bare zinc electrode, indicating that the battery containing the COF@Zn electrode has a higher capacity and good electrochemical reaction activity.
[0071] 10. Rate performance diagram of full battery composed of pure zinc foil and zinc foil with protective film
[0072] like Fig.11 As shown, COF@Zn||δ-MnO 2 The battery is better than bare Zn||δ-MnO 2 The battery has better rate performance, which can be attributed to the COF@Zn||δ-MnO 2 Batteries have a small charge transfer resistance.
[0073] 11. Long cycle stability diagram of full battery composed of pure zinc foil and zinc foil with protective film
[0074] like Fig.12 , at 100mAg -1 At a current density of 1.34 W, COF@Zn||δ-MnO 2 The battery showed better cycling stability, with a capacity retention of 75% after 500 cycles. 2 The discharge capacity of the battery dropped sharply after 100 cycles, which may be due to the growth of zinc dendrites and the formation of ZHS during the charge and discharge process, which reduced the number of available zinc ions. It can be seen that the COF protective layer can inhibit zinc dendrites and side reactions, thereby significantly improving the COF@Zn||δ-MnO 2 The overall electrochemical performance of the battery.
[0075] Example 2
[0076] A controllable preparation method based on a covalent organic framework thin film material comprises the following steps: dissolving 10.5 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and 8.5 mg of 2,3,5,6-tetrafluoroterephthalaldehyde (TFTA) in a mixed solvent of 1,4-dioxane and mesitylene in a volume ratio of 3:2, and completely dissolving them by ultrasound as an organic phase; at the same time, adding 5 ml of 5 mM scandium trifluoromethanesulfonate as an aqueous phase to 50 ml of deionized water, slowly adding the aforementioned organic phase to the aqueous phase, and sealing the mixture at 25°C and standing for 48 hours; the obtained product is repeatedly washed with acetone and deionized water, respectively, and the thin film is transferred to a zinc foil by an acetone solvent drawing method, and then placed in a vacuum oven at 85°C and dried for 12 hours to obtain the desired electrode material.
[0077] The synthesis of FCOFs thin film material is as shown in the following route (2):
[0078]
[0079] The product obtained in Example 2 was tested and characterized for performance:
[0080] 1. Infrared spectrum of FCOFs materials
[0081] from Figure 2 It can be seen from the FTIR spectrum that 1614cm -1 The peak at 1705 cm-1 is attributed to the newly formed C=N imine stretching vibration. -1 The peak intensity at weakened, indicating that the aldehyde group of the TFTA monomer was consumed, further proving that the FCOFs material was successfully synthesized.
[0082] 2. X-ray diffraction analysis of FCOFs
[0083] like Fig.13 As shown, there is a very strong peak below 5°, which indicates the successful preparation of FCOFs material and the good crystallinity of the material.
[0084] 3. Tafel curve of half-cell composed of pure zinc foil and zinc foil with fluorine-based COF protective film
[0085] from Fig.14 It can be seen that the calculated corrosion potential (Ecorr) of bare Zn is lower than that of FCOF@Zn, but the corrosion current density is significantly lower than that of bare Zn. The above results prove that the FCOFs protective layer has the ability to inhibit side reactions and uncontrollable corrosion.
[0086] 4. Linear polarization curves (LSV) of half-cells composed of pure zinc foil and zinc foil with fluorine-based COF protective film
[0087] To further evaluate the ability of the NOS layer to inhibit HER, linear sweep voltammetry (LSV) tests were performed using a three-electrode system. Fig.15 As shown in the figure, at the same potential position, the current density of FCOF@Zn is significantly lower than that of bare Zn, indicating that the FCOF protective layer can effectively inhibit the H 2 of release.
[0088] 5. Long cycle diagram of symmetrical battery composed of pure zinc foil and zinc foil with fluorine-based COF protective film
[0089] like Fig.16 As shown in Figure 2, the FCOF@Zn||FCOF@Zn symmetric cell exhibits a long cycle life of ∼1200 h at 3 mA cm -2 and 1mAh cm -2 There is no obvious voltage fluctuation when cycling. In contrast, the Zn||Zn symmetric battery suddenly short-circuited after ~60h of cycling, and the corresponding plating-stripping overpotential showed a large voltage fluctuation amplitude, indicating that disordered dendrite growth caused irreversible damage. These results verify that the FCOF protective layer on the interface can establish a uniform electric field, avoid the formation of unfavorable nucleation, and thus extend the cycle life of the battery.
[0090] 6. Cyclic voltammetry (CV) curves of full batteries composed of pure zinc foil and zinc foil with fluorine-based COF protective film
[0091] To evaluate the practical application of FCOF@Zn anode, we further assembled and evaluated 2 A full cell consisting of a cathode and a FCOF@Zn anode. Fig.17 In the CV curve, there are two pairs of redox peaks, representing the typical Zn 2+ In MnO 2 The embedding and ejection process.
[0092] 7. Rate performance diagram of full battery composed of pure zinc foil and zinc foil with fluorine-based COF protective film
[0093] from Fig.18 From the perspective of the rate performance of the full battery, FCOF@Zn||MnO 2 The battery is better than Zn||MnO at various current density values. 2 The battery showed higher capacity values, which indicates that Zn 2+ Rapid diffusion on the surface of the FCOF layer.
[0094] Application Examples
[0095] The prepared thin film material was transferred to zinc foil by acetone solvent drawing method and used as the negative electrode of button battery.
[0096] The aqueous zinc ion battery assembly method comprises the following steps:
[0097] MnO was prepared according to the literature method. 2 , and then pressed on the stainless steel foil current collector by coating, and obtained circular thin slices with a radius of 0.55-0.8 mm as the positive electrode material of the battery by simple cutting; at the same time, the above-mentioned protected zinc foil was used as the negative electrode, the qualitative filter paper was used as the diaphragm, and the ZnSO 4 The solution is an electrolyte, a gasket and a shrapnel are added, and finally the aqueous zinc ion battery is assembled to obtain a zinc ion battery.
[0098] So far, COF thin film materials have been relatively rarely used in the negative electrode protection of aqueous zinc-ion batteries. Limited by the intrinsic properties of polymer materials, most materials are in powder form, which greatly limits the application of such materials in aqueous zinc-ion batteries.
[0099] The COF material provided by the present invention not only has multiple redox sites, but can also be prepared into a thin film by a simple method, which is transferred to a zinc foil by an acetone solvent drawing method, thereby protecting the negative electrode of an aqueous zinc ion battery.
[0100] At the same time, it is not limited to water systems, but also protects the negative electrodes of organic lithium, sodium, calcium, magnesium, aluminum, and iodine ion batteries. Among them, zinc as a negative electrode material has a capacity of 820 mAh g -1 High theoretical capacity with a low electrode potential of -0.76V.
[0101] The above embodiments of the present invention are only examples of better implementation of the present invention and are not intended to limit the present invention. Any equivalent replacement, modification or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A structure of a covalent organic framework COFs thin film material is:
2. A method for preparing a covalent organic framework COFs thin film material according to claim 1, characterized in that: Compounds containing aldehyde groups and amino groups were used as monomers respectively, and Schiff base reaction was utilized to prepare COFs, a negative electrode protection material for aqueous zinc ion batteries, through liquid-liquid interfacial polymerization.
3. The method for preparing a covalent organic framework COFs thin film material according to claim 2, characterized in that: In the phenyl compounds containing aldehyde functional groups, heteroatoms F atoms, N atoms, or Cl atoms are introduced to regulate the charge distribution of the entire monomer molecule, so as to protect the zinc negative electrode while regulating the zinc foil crystal surface, making it more conducive to Zn 2+ The horizontally deposited crystal faces are exposed.
4. The method for preparing a covalent organic framework COFs thin film material according to claim 2 or 3, characterized in that: There are 6 kinds of phenyl compounds containing amino functional groups, which react with 6 kinds of monomers containing aldehyde groups respectively. By controlling their molar amounts, they react fully with the aldehyde monomers to prepare a film with uniform thickness; wherein the aldehyde monomers are: The amine monomers are: X is C or N.
5. The method for preparing a covalent organic framework COFs thin film material according to claim 4, characterized in that: When preparing thin film materials by interfacial polymerization, the mass ratio of the two reaction monomers is 3.75-15.7:4.4-20.8 mg, the reaction temperature is 25-30° C., and the reaction time is 48-72 h.
6. An application of the covalent organic framework (COFs) thin film material according to claim 5 in protecting the negative electrode of an aqueous zinc ion battery.
7. The method for applying a covalent organic framework COFs thin film material in protecting the negative electrode of an aqueous zinc ion battery according to claim 6, characterized in that: The prepared film material is covered on the zinc foil by acetone solvent drawing method, left to stand at room temperature to allow the acetone to fully evaporate, then thoroughly washed with deionized water, and finally placed in an oven for drying. The size of the film is cut and matched according to the size of the zinc foil.
8. The method for applying a covalent organic framework (COFs) thin film material in protecting the negative electrode of an aqueous zinc ion battery according to claim 7, characterized in that: The zinc foil is replaced by stainless steel foil, copper foil or titanium foil.
Citation Information
Patent Citations
Preparation method and application of zinc negative electrode modified by covalent organic framework material
CN113725421A
Method for preparing covalent organic framework composite membrane through confinement interfacial polymerization reaction and application of covalent organic framework composite membrane
CN116020285A
Cited By
Zinc pole piece coated with sulfonyl COF membrane, preparation method of zinc pole piece and aqueous zinc battery
CN120473485A